CMET-38. PREVALENCE AND SURVIVAL OUTCOMES OF UROTHELIAL CARCINOMA BRAIN METASTASES. (11th November 2019) - Kavouridis, Vasileios; Harary, Maya; Smith, Timothy; Braun, David; Iorgulescu, Bryan
Abstract: BACKGROUND: Urothelial carcinoma is a common malignancy with 79, 000 new cases diagnosed annually. However, urothelial brain metastases (UBM) are encountered uncommonly. Herein we evaluate their national prevalence, predictors, and treatment outcomes in the contemporary era. METHODS: The characteristics, management, and overall survival (OS) of UBM patients (2010–2015) were evaluated using the National Cancer Database, which comprises >70% of all newly diagnosed cancers in the U.S. OS was analyzed with Kaplan-Meier methods and log-rank tests. National outcomes were compared to our institutional cohort of UBMs. RESULTS: Out of 208, 600 patients diagnosed with urothelial carcinoma, 8.4% presented with stage IV disease–of these only 216 (1.2%) had BMs at the time of diagnosis. Patients presenting with bone, liver, or lung metastases were more likely to present with synchronous BMs. Brain involvement demonstrated significantly worse median OS (3.9mos, 95%CI: 3.1–4.9) than non-BM stage IV disease (10.9mos, 95%CI: 10.6–11.2, p< 0.001). Compared to non-BM stage IV disease, UBMs were more likely to have surgery for metastatic disease and receive radiotherapy (p< 0.001); but were less likely to have primary resection or chemotherapy. In multivariable analysis of stage IV urothelial cancer, BMs demonstrated significantly worse OS (HR 1.43, 95%CI: 1.20–1.72, p< 0.001). In our institutional data, 10 urothelial cancer patients developed BMs; of which 7 were male, median age and KPS at diagnosis were 64.9yo (IQR 56.4–72.0) and 85 (IQR 75–100). Four patients had synchronous metastases; the median number of BM lesions was 2 (IQR 1–2), with a median size of 2.6cm (IQR 1.6–3.3). All 10 underwent GTR, 3 also with SRS and 7 with WBRT, associated with a median OS of 16.5mos. CONCLUSIONS: Our results confirm the rarity of UBMs and suggest that BM screening may only be indicated in stage IV patients with neurological symptoms. Systemic therapies demonstrate improved OS in these patients.